Evaluating the feasibility and efficacy of the Amsterdam memory and attention training for children (Amat-c) following acquired brain injury (ABI): protocol for a pilot study with online clinician support. Issue 3 (29th December 2022) - Catroppa, Cathy; Botchway, Edith; Ryan, Nicholas P.; Anderson, Vicki; Morrison, Elle; Lam, Bernadette; Piazza, Chandelle; Krasts, Daina; McIntosh, Emma; Khan, Noor; Sood, Nikita
Abstract: Background: Attention and memory deficits are common following paediatric acquired brain injury (ABI). However, there are few evidence-based interventions to improve these domains and benefit the everyday life of children post-injury. The Amsterdam Memory and Attention Training for children (Amat-c) has been translated from Dutch to English and shown to improve attention and memory skills in children following ABI. This protocol describes a study to expand accessibility of the program by using online, clinician-supported delivery with children post-ABI. Method/design: The study is a randomized controlled trial. Participants will be 40 children aged 8–16 a minimum of one-year post-ABI. Participants in the treatment group will complete 18 weekly sessions of the Amat-c program with weekly online clinician support. Participants in the active-control group will be administered ABI psychoeducation via a booklet for parents, with weekly online clinician contact. Attention and memory will be assessed at three time points up to six months post-intervention. Results: Analysis will be repeated measures multivariate planned comparisons; using the Statistical Package for the Social Sciences (IBM SPSS Statistics) General Linear Model procedure will compare pre- and post-intervention and six-month follow-up outcomes. Discussion: If shown efficacious in improving attention and memory, our team will then take a key role in implementing Amat-c into clinical care.